2024
DOI: 10.1002/aenm.202302786
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Microporous Transport Layers: Implications for Low Catalyst Loadings, Thin Membranes, and High Current Density Operation for Proton Exchange Membrane Electrolysis

Tobias Schuler,
Carl Cesar Weber,
Jacob A. Wrubel
et al.

Abstract: Porous transport layers (PTL) and their surface properties have the potential to improve the performance of proton exchange membrane water electrolyzers (PEMWE), which is imperative to reduce feedstock costs and lead to their widespread implementation. This work introduces a novel generation of titanium microporous layers (MPLs) with ultra‐low thicknesses of ≈20 µm which reduces raw material costs. They also feature advanced interfacial properties tailored to maximize catalyst utilization at low Ir‐loadings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…As a result, the Tafel slopes reduce with addition of the MPL, from 54.3 to 44.0 mV dec −1 for commercial sintered Ti fiber PTL and from 47.4 to 44.3 mV dec −1 for commercial Ti powder PTL. A similar observation has been made by Schuler et al, 22,29 where lower Tafel slope was observed for their MPLs compared to the bare PTL substrate. The mass transport loss of MPL/PTL bilayers remained similar to the commercial sintered Ti powder PTL for the range of current densities tested in this work, Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, the Tafel slopes reduce with addition of the MPL, from 54.3 to 44.0 mV dec −1 for commercial sintered Ti fiber PTL and from 47.4 to 44.3 mV dec −1 for commercial Ti powder PTL. A similar observation has been made by Schuler et al, 22,29 where lower Tafel slope was observed for their MPLs compared to the bare PTL substrate. The mass transport loss of MPL/PTL bilayers remained similar to the commercial sintered Ti powder PTL for the range of current densities tested in this work, Fig.…”
Section: Resultssupporting
confidence: 87%
“…Other efforts include vacuum plasma spray deposition of a support layer on commercial and mesh-type PTLs. 21,[23][24][25][26] Similarly, Schuler et al 22,29 showed that a Ti MPL improves electrolyzer performance, and the CL/PTL interface is a crucial MPL property. However, the MPLs reported to date did not have tunable pore size at the CL/PTL interface, which is a key parameter to find the optimal MPL structure.…”
mentioning
confidence: 99%
“…Using the mean surface roughness metric, the addition of an MPL improves the surface roughness by a factor of ≈3 compared to a pristine PTL (4.4 μm vs 14.2 μm for the MPL and PTL, respectively; see second row in Table I). In comparison, Schuler et al 8,15,18 reported R m values of 22-139 μm for seven different fiber-based PTLs, 28-31 μm for two powdersintered PTLs, and 11-26 μm for five different MPLs. Accordingly, the surface roughness of the PTL investigated in the present work is already significantly smoother than other PTLs studied in the literature, and lying more in the range of MPLs fabricated by other groups, while the MPL prepared here is even less rough.…”
Section: Resultsmentioning
confidence: 97%
“…In recent years, some work has been accomplished towards developing pore-graded, two-layer PTLs for PEMWEs, differently named by different groups: PTL with backing layer, 12 pore-graded PTL, 13 spatially-graded PTL, 14 or hierarchically structured PTL. 15 The layer with the smaller pores is also called microporous layer (MPL), 7,[15][16][17][18] analogous to the naming that had been adopted in the PEM fuel cell literature, where a ≈20-40 μm thick carbon blackbased MPL with ≈0.1-1 μm pores is usually applied onto a ≈100-200 μm thick carbon fiber substrate with ≈10-40 μm pores. 19,20 In the following, we will refer to the large-pore substrate as PTL and to a pore-graded, two-layer PTL as PTL/MPL.…”
mentioning
confidence: 99%
“…The microporous layer (MPL) has been a groundbreaking discovery that enhanced both interfacial contact and mass transport in proton-exchange-membrane fuel cells. These MPLs are fabricated by coating carbon particles over carbon-fiber-based gas diffusion layers. Such success of MPLs in fuel cells have led to the development of MPLs for water electrolyzers, which resulted in significant improvement of catalyst utilization. However, the difficulty and associated high cost in processing titanium, which requires high temperature at inert atmosphere, limit the flexibility in designing MPLs to optimize interfacial contact and mass transport for water electrolyzers . MPLs have been used for other applications, as well.…”
Section: Introductionmentioning
confidence: 99%